Attentional biases in patients suffering from unipolar depression: results of a dot probe task investigation - Trapp, Wolfgang; Kalzendorf, Christoph; Baum, Corinna; Hajak, Göran; Lautenbacher, Stefan (Psychiatry research, 2018)
Cognitive models of depression emphasize the relevance of cognitive biases for development, onset and maintenance of major depressive disorder (MDD). Attentional biases consisting of increased attention to negative, mood congruent stimuli and reduced attention to positive, mood-incongruent stimuli are postulated but have rarely been tested for early attentional processing. Furthermore, the role of concurrent depressive mood as a moderating factor has not been studied to date. Participants comprised 30 patients suffering from MDD and 30 healthy control subjects. All participants performed a dot-probe task with pictorial stimuli displaying affective facial expressions, presented either for 100ms or for 500ms. Attentional biases towards faces displaying joy in both MDD patients and control subjects and towards faces displaying pain in MDD subjects were found at presentation times of 100ms. In the MDD sample, the bias indices at 100ms were correlated with concurrent depressive mood. In patients with pronounced depressive mood, significant biases towards happy and angry faces were observed that exceed the biases obtained in control subjects and patients with less depressive mood. The results provide first evidence that MDD patients with pronounced depressive mood show an increased early attentional engagement towards emotional salient stimuli, independent from valence. •Usually, depressive patients show mood congruent cognitive biases.•However, we found early attentional biases towards positive and negative emotions.•In severely depressed patients, these biases were stronger than in healthy controls.•Hence, during initial engagement, emotional salience might be more most important.